Status gondok berhubungan dengan pola menstruasi dan kejadian anemia pada wanita usia subur di daerah endemik GAKY - Ori Pertami Enardi; Untung S. Widodo; Detty Siti Nurdiati (Alma Ata University Press, 2014)
ABSTRACTBackground: Iodine deficiency disorder (IDD) is one of health problems in Indonesia that has major impact on survival and quality of human resources. Iodine is an essential component of thyroid hormone, meanwhile thyroid hormone has an important role in reproductive function. Nutritional anemia is also a nutrition problem in Indonesia. Thyroid hormone deficiency may cause disorder in hemoglobin synthesis due to lack of thyroxine hormone and the incidence of intestine failure to absorb Fe. In hypothyroid condition, the amount of gastric acid secretion will decrease that disrupts absorption of nutrients, including Fe.Objectives: To identify association between goitre status and menstruation pattern and the incidence of anemia in legible women at IDD endemic area of Kenagarian Siguntur Subdistrict of Sitiung District of Dharmasraya Province of Sumatera Barat.Methods: The study was observational with cross sectional design that was carried out at Kenagarian Siguntur Subdistrict of Sitiung District of Tanah Datar. Subject of the study were 154 legible women with inclusion criteria 20-40 years old and willing to become respondent and have blood examination. Samples were taken using simple random sampling method. Data analysis used chi-square and logistic regression.Results: The result of data analysis showed that some respondents had goitre (29.9%), menstruation problem (35.1%), and were anemic (37.0%). The result of statistical analysis showed that there was association between goitre status and menstruation pattern (OR: 6.562, 95% CI: 3.076-13.99, p<0.005) and anemia (OR: 3.229, 95% CI: 1.577-6.612, p<0.005).Conclusions: Goitre status had significant association with menstruation pattern and the incidence of anemia.KEYWORDS: iodine deficiency disorder (IDD), menstruation pattern, anemiaABSTRAKLatar belakang: Gangguan akibat kekurangan yodium (GAKY) di Indonesia merupakan salah satu masalah kesehatan. Hal ini disebabkan yodium merupakan komponen penting hormon tiroid, yang juga berperan penting dalam fungsi reproduksi. Defisiensi hormon tiroid dapat mengakibatkan gangguan sintesis hemoglobin dan absorbs besi di usus.Tujuan: Mengetahui hubungan status gondok dengan pola menstruasi dan kejadian anemia pada wanita usia subur daerah endemik GAKY di Kenagarian Siguntur Kecamatan Sitiung Kabupaten Dharmasraya Propinsi Sumatera Barat.Metode: Jenis penelitian ini adalah observasional dengan menggunakan rancangan penelitian cross sectional, yang dilakukan di Kenegarian Siguntur Kecamatan Sitiung Kabupaten Tanah Datar. Subjek penelitian ini adalah 154 orang wanita usia subur yang dipilih menggunakan metode simple random sampling. Analisis data dilakukan dengan uji chi-square dan regresi logistik.Hasil: Wanita usia subur yang menderita gondok, mengalami gangguan menstruasi, dan kejadian anemia berturut-turut sebesar 29,9%, 35,1%, dan 37,0%. Hasil uji statistik menunjukkan ada hubungan antara status gondok dengan pola menstruasi (x2=26,191, OR: 6,563, 95% CI: 3,076-13,99, p<0,001) dan anemia (x2=10,708, OR: 3,229,95% CI: 1,577-6,612, p<0,005).Kesimpulan: Status gondok mempunyai hubungan yang signifikan dengan pola menstruasi dan kejadian anemia.KATA KUNCI: gangguan akibat kekurangan yodium (GAKY), pola menstruasi, anemia